The Relationship between Corporate Social Responsibility and Financial Performance: Evidence from Vietnam Textile and Garment Industry - Thi Thu Hien Phan (International Journal of Small and Medium Enterprises and Business Sustainability, 2019)
The direct relationship between corporate social responsibility (CSR) and financial performance has been investigated by many researchers, but direct testing seems to be inaccurate as it is difficult to explain their findings. Because there are many factors indirectly affect this relationship. This study examines corporate reputation, customer loyalty, and employee engagement as mediate variables in the relationship between CSR and financial performance. Sample is 389 garment enterprises in Vietnam show that the link between CSR and financial efficiency is the intermediate relationship. The positive effect of CSR on financial performance is due to the positive impact of CSR on the company's reputation, customer satisfaction, and employee engagement.